Gingival Biotype: A Secret for Esthetic Success - Sarma, Marjita; Shenoy, Nina; Bhandary, Rahul (Journal of Health and Allied Sciences NU, 2021)
Gingival biotype, in the recent years, has gained substantial interest as one of the important pillars for esthetic success. This review provides recommendations to be considered prior to performing any dental procedure to attain best clinical results. Several methods for measuring biotype have been suggested. Gingiva is often subjected to various insults during routine dental procedures. Hence, understanding the gingival biotype can provide insights into precautions rendered necessary during tissue handling to avoid undesirable treatment outcomes.
Keywords: gingival biotype; gingival thickness; TRAN